Droplet size distribution in a biphasic liquid reactor for understanding the impact of various dual impeller designs on the morphology of S-PVC - Park, Jeil; Lee, Wonhyeong; Lee, Jae W. (The Korean journal of chemical engineering, 2023)
This study investigated the effect of dual impeller geometry on the droplet size in the suspension-PVC (S-PVC) polymerization process. To simulate the process, 1,2-dichloroethane was used as a dispersed phase, because it has been used to replace the toxic vinyl chloride monomer (VCM). Using a borescope method, a droplet size was measured for a biphasic liquid system, and the Sauter mean diameter increased by 46.5% as the upper paddle impeller was replaced by 20° pitched paddle. It also increased when the impeller diameter and the blade width increased. Considering this effect, a geometrical factor (F) was revised, and a calculated maximum energy dissipation rate was used for establishing the Sauter mean diameter correlation. The proposed correlation can estimate the Sauter mean diameter within ±20% error, and one can predict the normality of the polymerization under specific impeller geometry using this correlation.